2012
DOI: 10.1007/s13209-012-0095-6
|View full text |Cite
|
Sign up to set email alerts
|

A chronology of turning points in economic activity: Spain, 1850–2011

Abstract: This paper codifies in a systematic and transparent way a historical chronology of business cycle turning points for Spain reaching back to 1850 at annual frequency, and 1939 at monthly frequency. Such an exercise would be incomplete without assessing the new chronology itself and against others-this we do with modern statistical tools of signal detection theory. We also use these tools to determine which of several existing economic activity indexes provide a better signal on the underlying state of the econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…The 1994–2007 expansion was the longest uninterrupted period of growth in Spain since at least 1850, see Berge and Jordá (). Gross domestic products (GDP) grew at an average rate of 3.5% per year, which compares favorably to the EU average of 2.2% over the same period.…”
Section: Introductionmentioning
confidence: 99%
“…The 1994–2007 expansion was the longest uninterrupted period of growth in Spain since at least 1850, see Berge and Jordá (). Gross domestic products (GDP) grew at an average rate of 3.5% per year, which compares favorably to the EU average of 2.2% over the same period.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because the analysis of the manufacturing industry cycle has not yet been done. In Spain and in the field as a whole, we highlight works such as that by Bergé and Jordà (2013), Dolado, Sebastián and Vallés (1993), Belaire-Franch and Contreras (2002), Doménech and Gómez (2005) or Doménech, Estrada and Gozález-Calbet (2007). In a study on the variations observed in Spanish business cycles after integration, we find Pérez, Escriche and García (2007) or Gardeazábal and Iglesias (2000).…”
Section: Cyclical Fluctuations In Economic Variables Have Considerablmentioning
confidence: 99%
“…Rule based models are generally easy to understand and implement but suffer from delayed state identification due to the information lag. By contrast MS models are perhaps less intuitive, but produce immediate results (Berge and Jordà, 2013). Under such fully specified models the current state can be judged on the basis of probability, and future states can be forecast.…”
Section: Markov Switching (Ms)mentioning
confidence: 99%